Application of ionizing radiation as an elicitor to enhance the growth and metabolic activities in Chlamydomonas reinhardtii - Kim, Jin-Hong; Dubey, Shubham Kumar; Hwangbo, Kwon; Chung, Byung Yeoup; Lee, Seung Sik; Lee, Sungbeom (Frontiers in Plant Science, 2023)
Chlamydomonas reinhardtii is a eukaryotic, unicellular photosynthetic organism and a potential algal platform for producing biomass and recombinant proteins for industrial use. Ionizing radiation is a potent genotoxic and mutagenic agent used for algal mutation breeding that induces various DNA damage and repair responses. In this study, however, we explored the counterintuitive bioeffects of ionizing radiation, such as X- and γ-rays, and its potential as an elicitor to facilitate batch or fed-batch cultivation of Chlamydomonas cells. A certain dose range of X- and γ-rays was shown to stimulate the growth and metabolite production of Chlamydomonas cells. X- or γ-irradiation with relatively low doses below 10 Gy substantially increased chlorophyll, protein, starch, and lipid content as well as growth and photosynthetic activity in Chlamydomonas cells without inducing apoptotic cell death. Transcriptome analysis demonstrated the radiation-induced changes in DNA damage response (DDR) and various metabolic pathways with the dose-dependent expression of some DDR genes, such as CrRPA30, CrFEN1, CrKU, CrRAD51, CrOASTL2, CrGST2, and CrRPA70A. However, the overall transcriptomic changes were not causally associated with growth stimulation and/or enhanced metabolic activities. Nevertheless, the radiation-induced growth stimulation was strongly enhanced by repetitive X-irradiation and/or subsequent cultivation with an inorganic carbon source, i.e., NaHCO3, but was significantly inhibited by treatment of ascorbic acid, a scavenger of reactive oxygen species (ROS). The optimal dose range of X-irradiation for growth stimulation differed by genotype and radiation sensitivity. Here, we suggest that ionizing radiation within a certain dose range determined by genotype-dependent radiation sensitivity could induce growth stimulation and enhance metabolic activities, including photosynthesis, chlorophyll, protein, starch, and lipid synthesis in Chlamydomonas cells via ROS signaling. The counterintuitive benefits of a genotoxic and abiotic stress factor, i.e., ionizing radiation, in a unicellular algal organism, i.e., Chlamydomonas, may be explained by epigenetic stress memory or priming effects associated with ROS-mediated metabolic remodeling.